products/sources/formale Sprachen/Delphi/Agenda 1.1/Auslieferung image not shown  

Quellcode-Bibliothek

© Kompilation durch diese Firma

[Weder Korrektheit noch Funktionsfähigkeit der Software werden zugesichert.]

Datei:   Sprache: Unknown

(*  Title:      HOL/Proofs/Lambda/Commutation.thy
    Author:     Tobias Nipkow
    Copyright   1995  TU Muenchen
*)


section \<open>Abstract commutation and confluence notions\<close>

theory Commutation
imports Main
begin

declare [[syntax_ambiguity_warning = false]]


subsection \<open>Basic definitions\<close>

definition
  square :: "['a => 'a => bool, 'a => 'a => bool, 'a => 'a => bool, 'a => 'a => bool] => bool" where
  "square R S T U =
    (\<forall>x y. R x y --> (\<forall>z. S x z --> (\<exists>u. T y u \<and> U z u)))"

definition
  commute :: "['a => 'a => bool, 'a => 'a => bool] => bool" where
  "commute R S = square R S S R"

definition
  diamond :: "('a => 'a => bool) => bool" where
  "diamond R = commute R R"

definition
  Church_Rosser :: "('a => 'a => bool) => bool" where
  "Church_Rosser R =
    (\<forall>x y. (sup R (R\<inverse>\<inverse>))\<^sup>*\<^sup>* x y \<longrightarrow> (\<exists>z. R\<^sup>*\<^sup>* x z \<and> R\<^sup>*\<^sup>* y z))"

abbreviation
  confluent :: "('a => 'a => bool) => bool" where
  "confluent R == diamond (R\<^sup>*\<^sup>*)"


subsection \<open>Basic lemmas\<close>

subsubsection \<open>\<open>square\<close>\<close>

lemma square_sym: "square R S T U ==> square S R U T"
  apply (unfold square_def)
  apply blast
  done

lemma square_subset:
    "[| square R S T U; T \ T' |] ==> square R S T' U"
  apply (unfold square_def)
  apply (blast dest: predicate2D)
  done

lemma square_reflcl:
    "[| square R S T (R\<^sup>=\<^sup>=); S \ T |] ==> square (R\<^sup>=\<^sup>=) S T (R\<^sup>=\<^sup>=)"
  apply (unfold square_def)
  apply (blast dest: predicate2D)
  done

lemma square_rtrancl:
    "square R S S T ==> square (R\<^sup>*\<^sup>*) S S (T\<^sup>*\<^sup>*)"
  apply (unfold square_def)
  apply (intro strip)
  apply (erule rtranclp_induct)
   apply blast
  apply (blast intro: rtranclp.rtrancl_into_rtrancl)
  done

lemma square_rtrancl_reflcl_commute:
    "square R S (S\<^sup>*\<^sup>*) (R\<^sup>=\<^sup>=) ==> commute (R\<^sup>*\<^sup>*) (S\<^sup>*\<^sup>*)"
  apply (unfold commute_def)
  apply (fastforce dest: square_reflcl square_sym [THEN square_rtrancl])
  done


subsubsection \<open>\<open>commute\<close>\<close>

lemma commute_sym: "commute R S ==> commute S R"
  apply (unfold commute_def)
  apply (blast intro: square_sym)
  done

lemma commute_rtrancl: "commute R S ==> commute (R\<^sup>*\<^sup>*) (S\<^sup>*\<^sup>*)"
  apply (unfold commute_def)
  apply (blast intro: square_rtrancl square_sym)
  done

lemma commute_Un:
    "[| commute R T; commute S T |] ==> commute (sup R S) T"
  apply (unfold commute_def square_def)
  apply blast
  done


subsubsection \<open>\<open>diamond\<close>, \<open>confluence\<close>, and \<open>union\<close>\<close>

lemma diamond_Un:
    "[| diamond R; diamond S; commute R S |] ==> diamond (sup R S)"
  apply (unfold diamond_def)
  apply (blast intro: commute_Un commute_sym) 
  done

lemma diamond_confluent: "diamond R ==> confluent R"
  apply (unfold diamond_def)
  apply (erule commute_rtrancl)
  done

lemma square_reflcl_confluent:
    "square R R (R\<^sup>=\<^sup>=) (R\<^sup>=\<^sup>=) ==> confluent R"
  apply (unfold diamond_def)
  apply (fast intro: square_rtrancl_reflcl_commute elim: square_subset)
  done

lemma confluent_Un:
    "[| confluent R; confluent S; commute (R\<^sup>*\<^sup>*) (S\<^sup>*\<^sup>*) |] ==> confluent (sup R S)"
  apply (rule rtranclp_sup_rtranclp [THEN subst])
  apply (blast dest: diamond_Un intro: diamond_confluent)
  done

lemma diamond_to_confluence:
    "[| diamond R; T \ R; R \ T\<^sup>*\<^sup>* |] ==> confluent T"
  apply (force intro: diamond_confluent
    dest: rtranclp_subset [symmetric])
  done


subsection \<open>Church-Rosser\<close>

lemma Church_Rosser_confluent: "Church_Rosser R = confluent R"
  apply (unfold square_def commute_def diamond_def Church_Rosser_def)
  apply (tactic \<open>safe_tac (put_claset HOL_cs \<^context>)\<close>)
   apply (tactic \<open>
     blast_tac (put_claset HOL_cs \<^context> addIs
       [@{thm sup_ge2} RS @{thm rtranclp_mono} RS @{thm predicate2D} RS @{thm rtranclp_trans},
        @{thm rtranclp_converseI}, @{thm conversepI},
        @{thm sup_ge1} RS @{thm rtranclp_mono} RS @{thm predicate2D}]) 1\<close>)
  apply (erule rtranclp_induct)
   apply blast
  apply (blast del: rtranclp.rtrancl_refl intro: rtranclp_trans)
  done


subsection \<open>Newman's lemma\<close>

text \<open>Proof by Stefan Berghofer\<close>

theorem newman:
  assumes wf: "wfP (R\\)"
  and lc: "\a b c. R a b \ R a c \
    \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d"
  shows "\b c. R\<^sup>*\<^sup>* a b \ R\<^sup>*\<^sup>* a c \
    \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d"
  using wf
proof induct
  case (less x b c)
  have xc: "R\<^sup>*\<^sup>* x c" by fact
  have xb: "R\<^sup>*\<^sup>* x b" by fact thus ?case
  proof (rule converse_rtranclpE)
    assume "x = b"
    with xc have "R\<^sup>*\<^sup>* b c" by simp
    thus ?thesis by iprover
  next
    fix y
    assume xy: "R x y"
    assume yb: "R\<^sup>*\<^sup>* y b"
    from xc show ?thesis
    proof (rule converse_rtranclpE)
      assume "x = c"
      with xb have "R\<^sup>*\<^sup>* c b" by simp
      thus ?thesis by iprover
    next
      fix y'
      assume y'c: "R\<^sup>*\<^sup>* y' c"
      assume xy': "R x y'"
      with xy have "\u. R\<^sup>*\<^sup>* y u \ R\<^sup>*\<^sup>* y' u" by (rule lc)
      then obtain u where yu: "R\<^sup>*\<^sup>* y u" and y'u: "R\<^sup>*\<^sup>* y' u" by iprover
      from xy have "R\\ y x" ..
      from this and yb yu have "\d. R\<^sup>*\<^sup>* b d \ R\<^sup>*\<^sup>* u d" by (rule less)
      then obtain v where bv: "R\<^sup>*\<^sup>* b v" and uv: "R\<^sup>*\<^sup>* u v" by iprover
      from xy' have "R\\ y' x" ..
      moreover from y'u and uv have "R\<^sup>*\<^sup>* y' v" by (rule rtranclp_trans)
      moreover note y'c
      ultimately have "\d. R\<^sup>*\<^sup>* v d \ R\<^sup>*\<^sup>* c d" by (rule less)
      then obtain w where vw: "R\<^sup>*\<^sup>* v w" and cw: "R\<^sup>*\<^sup>* c w" by iprover
      from bv vw have "R\<^sup>*\<^sup>* b w" by (rule rtranclp_trans)
      with cw show ?thesis by iprover
    qed
  qed
qed

text \<open>
  Alternative version.  Partly automated by Tobias
  Nipkow. Takes 2 minutes (2002).

  This is the maximal amount of automation possible using \<open>blast\<close>.
\<close>

theorem newman':
  assumes wf: "wfP (R\\)"
  and lc: "\a b c. R a b \ R a c \
    \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d"
  shows "\b c. R\<^sup>*\<^sup>* a b \ R\<^sup>*\<^sup>* a c \
    \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d"
  using wf
proof induct
  case (less x b c)
  note IH = \<open>\<And>y b c. \<lbrakk>R\<inverse>\<inverse> y x; R\<^sup>*\<^sup>* y b; R\<^sup>*\<^sup>* y c\<rbrakk>
                     \<Longrightarrow> \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d\<close>
  have xc: "R\<^sup>*\<^sup>* x c" by fact
  have xb: "R\<^sup>*\<^sup>* x b" by fact
  thus ?case
  proof (rule converse_rtranclpE)
    assume "x = b"
    with xc have "R\<^sup>*\<^sup>* b c" by simp
    thus ?thesis by iprover
  next
    fix y
    assume xy: "R x y"
    assume yb: "R\<^sup>*\<^sup>* y b"
    from xc show ?thesis
    proof (rule converse_rtranclpE)
      assume "x = c"
      with xb have "R\<^sup>*\<^sup>* c b" by simp
      thus ?thesis by iprover
    next
      fix y'
      assume y'c: "R\<^sup>*\<^sup>* y' c"
      assume xy': "R x y'"
      with xy obtain u where u: "R\<^sup>*\<^sup>* y u" "R\<^sup>*\<^sup>* y' u"
        by (blast dest: lc)
      from yb u y'c show ?thesis
        by (blast del: rtranclp.rtrancl_refl
            intro: rtranclp_trans
            dest: IH [OF conversepI, OF xy] IH [OF conversepI, OF xy'])
    qed
  qed
qed

text \<open>
  Using the coherent logic prover, the proof of the induction step
  is completely automatic.
\<close>

lemma eq_imp_rtranclp: "x = y \ r\<^sup>*\<^sup>* x y"
  by simp

theorem newman'':
  assumes wf: "wfP (R\\)"
  and lc: "\a b c. R a b \ R a c \
    \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d"
  shows "\b c. R\<^sup>*\<^sup>* a b \ R\<^sup>*\<^sup>* a c \
    \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d"
  using wf
proof induct
  case (less x b c)
  note IH = \<open>\<And>y b c. \<lbrakk>R\<inverse>\<inverse> y x; R\<^sup>*\<^sup>* y b; R\<^sup>*\<^sup>* y c\<rbrakk>
                     \<Longrightarrow> \<exists>d. R\<^sup>*\<^sup>* b d \<and> R\<^sup>*\<^sup>* c d\<close>
  show ?case
    by (coherent
      \<open>R\<^sup>*\<^sup>* x c\<close> \<open>R\<^sup>*\<^sup>* x b\<close>
      refl [where 'a='a] sym
      eq_imp_rtranclp
      r_into_rtranclp [of R]
      rtranclp_trans
      lc IH [OF conversepI]
      converse_rtranclpE)
qed

end

[ Dauer der Verarbeitung: 0.70 Sekunden  (vorverarbeitet)  ]